169k views
2 votes
Evaluate 1 3 m − 1 − 1 2 n 3 1 ​ m−1− 2 1 ​ nstart fraction, 1, divided by, 3, end fraction, m, minus, 1, minus, start fraction, 1, divided by, 2, end fraction, n when m = 2 1 m=21m, equals, 21 and n = 1 2 n=12n, equals, 12.

User RyanH
by
5.7k points

1 Answer

3 votes

Answer:

0

Explanation:

Apparently, you want the value of ...


(1)/(3)m-1-(1)/(2)n = (m)/(3)-(n)/(2)-1\\\\=(21)/(3)-(12)/(2)-1=7-6-1\\\\=\boxed{0}

The value of the given expression for the given variable values is zero.

User Laurianne
by
5.2k points